Highway accelerated loading instrument (HALI) for concrete block pavement - Ling, Tung Chai (2006)
Pavement damage and axle load are very much related. Even though there are many studies evaluating this relationship, not many of them used a full scale experiment especially in concrete block pavement. This study is to develop on equipment which is named as Highway Accelerated Loading Instrument (HALI) to simulate the normal road axle load. This instrument is able to generalize different axle loads on the full-scale road pavements. Pavements constructed in this machine have been fully instrumented for the measurement of stress, strain and deformation. The tested pavement is restricted to repetitions of specific axle loads applied by this mechanically guided test wheel. However, the machine has the limitation on temperature control for the pavement under accelerated trafficking test. This paper will describe the development of HALI and its application to the studies on behavior and performance of concrete block pavement.